Peningkatan Kualitas Pakan Ruminansia Melalui Teknologi Amoniasi Dan Silase Pada Kelompok Tani Ternak Sinar Terang Desa Bagik Polak Lombok Barat - Muhamad Amin; Syamsul Hidayat Dilaga; Dahlanuddin Dahlanuddin; Oscar Yanuarianto; Suhubdy Suhubdy (Universitas Mataram, 2026)
Feed availability and quality remain major constraints in smallholder cattle production systems in West Nusa Tenggara, particularly during the dry season. Low-quality crop residues such as rice straw are characterized by high fiber fractions and low crude protein content, resulting in poor digestibility and limited animal performance. This community engagement program aimed to enhance the quality and utilization of local feed resources ( rice straw and field grass) through ammoniation and silage technologies at the Sinar Terang Farmer Group, Bagik Polak Village, West Lombok. Activities included technical training, demonstration plots, and assisted feed processing using urea-based ammoniation and anaerobic silage fermentation. Evaluation was conducted organoleptically, including assessment of color, aroma, texture, and animal acceptability. Ammoniated corn straw showed a change in color to brownish-yellow, softer texture, and mild ammonia odor without spoilage. Silage exhibited green-brown coloration, compact structure, and a fresh acidic smell indicative of lactic acid fermentation. Theoretical analysis based on recent scientific literature indicates that ammoniation improves fiber degradability by disrupting lignin–cellulose bonds and increases nitrogen availability for rumen microbes, potentially improving crude protein equivalent and digestibility. Silage fermentation stabilizes nutrients, reduces dry matter losses, and enhances palatability through lactic acid production. The program improved farmers’ technical capacity and increased awareness of sustainable feed preservation strategies. These technologies represent practical and scalable solutions for improving ruminant productivity under smallholder conditions